Dissimilarities of neural representations of extinction trials are associated with extinction learning performance and renewal level - Lissek, Silke; Tegenthoff, Martin (Frontiers in Behavioral Neuroscience, 2024)
Renewal of extinguished responses is associated with higher activity in specific extinctionrelevant brain regions, i.e. hippocampus (HC), inferior frontal gyrus (IFG) and ventromedial PFC (vmPFC). HC is involved in processing of context information, while IFG and vmPFC use such context information for selecting and deciding among competing response options. However, it is as yet unknown to what extent trials with changed versus unchanged outcome, or extinction trials that evoke renewal (i.e. extinction context differs from acquisition and test context: ABA trials) and trials that do not (i.e. same context in all phases: AAA trials) are represented differentially in extinction-relevant brain regions. In this study, we applied representational similarity analysis (RSA) to determine differences in neural representations of these trial types and their relationship to extinction error rates and renewal level. Overall, individuals with renewal (REN) and those without (NoREN) did not differ significantly in their discrimination levels between ABA and AAA extinction trials, with the exception of right posterior HC, where REN exhibited more pronounced context-related discrimination. In addition, higher dissimilarity of representations in bilateral posterior HC, as well as in several IFG regions, during extinction learning was linked to lower ABA renewal rates. Both REN and NoREN benefitted from prediction error feedback from ABA extinction errors for context-and outcome-related discrimination of trials in IFG, vmPFC and HC, but only the NoREN group also benefitted from error feedback from AAA extinction errors. Thus, while in both groups the presence of a novel context supported formation of distinct representations, only in NoREN the expectancy violation of the surprising change of outcome alone had a similar effect. In addition, only in NoREN context-related discrimination was linked to error feedback in vmPFC. In summary, the findings show that context-and outcome-related discrimination of trials in HC, vmPFC and IFG is linked to extinction learning errors, regardless of renewal propensity, and at the same time point towards differential context processing strategies in REN and NoREN. Moreover, better discrimination of context-related trials during extinction learning promotes less renewal during extinction recall, suggesting that renewal may be related to suboptimal context-related trial discrimination.